2005
DOI: 10.1253/circj.69.273
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Course and Clinical Characteristics of Ventricular Tachycardia Detected in Children by School-Based Heart Disease Screening

Abstract: he incidence of ventricular tachycardia (VT) in childhood is low (0.2-0.8 per 10,000 children in school-based heart screening) compared with that in adults [1][2][3][4][5][6] in whom most VT is associated with coronary artery disease. In contrast, most pediatric cases are idiopathic without underlying heart disease and are found incidentally during school-based heart screening, with the exception of those found as complications of congenital heart diseases. The aim of the present study was to review the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 19 publications
0
44
0
7
Order By: Relevance
“…Zapadalność na utrwalony VT w ogólnej populacji pediatrycznej oceniono na 1/100 000 w ciągu 10 lat. Częstość występowania nieutrwalonego i utrwalonego VT również jest mała i wynosi 2-8/100 000 dzieci w wieku szkolnym [482,483].…”
Section: Definicje I Epidemiologiaunclassified
“…Zapadalność na utrwalony VT w ogólnej populacji pediatrycznej oceniono na 1/100 000 w ciągu 10 lat. Częstość występowania nieutrwalonego i utrwalonego VT również jest mała i wynosi 2-8/100 000 dzieci w wieku szkolnym [482,483].…”
Section: Definicje I Epidemiologiaunclassified
“…Nonsustained IVT originated mainly from the RV rather than the LV (P=0.001), which is consistent with an earlier study. 12 In the present study, 27% of IVT patients had nonsustained VT, which was different from school-based heart disease screening in Japan, describing that 90% in healthy children diagnosed as VT had nonsustained VT. 13 It is because our data was from a single tertiary hospital where most patients were referred from other hospitals and many of them had symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This case-control study investigated the association between IVA and SCN5A SNPs, in which overall 11 genetic variations including 5 novel and 6 previously identified ones were detected in 31 unrelated Chinese patients with IVA and 103 healthy controls. The study showed significant difference in distribution of c.87G>A and c.1673A>G between men and women in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%